Life on the wire: on tensegrity and force balance in cells - Galli, C.; Guizzardi, S.; Passeri, et al., G. (Acta Biomedica Atenei Parmensis, 2005)
Since cell mechanics has attracted the attention of a growing number of researchers, several models have been proposed to explain cell mechanical behavior, among which tensegrity is certainly the most convincing one. Originally developed by the architect Buckminster Fuller, tensegrity structures are based on the presence of discontinuous compression elements that balance the force generated by continuous tension elements, thus reaching an equilibrium that is completely independent of gravity. This model is a useful tool to predict cell spreading, motility and especially mechanotransduction, i.e. the capability to transform mechanical stresses into biochemical responses, a key process in homeostasis of many tissues that must continuously withstand mechanical forces, like bone, but which is still poorly understood.